The Role of Legal Consultation and Legal Aid Assistance for Disadvantaged Communities - Suryaningsi, Suryaningsi; Yulianingrum, Aullia Vivi; Mulawarman, Widyatmike Gede; Rosmini, Rosmini; Marwiah, Marwiah; Herliah, Endang (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2024)
The Constitution mandates that every person receive fair legal recognition, guarantees, protection and certainty as well as equal treatment before the law as the protection of human rights. Therefore, the government is responsible for providing legal assistance to poor people or groups of people as a manifestation of access to justice. Using a qualitative descriptive type with data collection techniques through observation, interviews and documentation with predetermined informants. Data analysis techniques consist of data collection, data reduction, data presentation and drawing conclusions or data verification. The subjects of this research are representatives of the management of the Law and Human Rights Council in 9 Regencies and Cities in East Kalimantan as Seekers of Justice. Next, the data obtained is used to analyze roles. The research results show that initial knowledge about the existence of Posbakum is limited within the 'Aisyiyah Organization, highlighting the need for increased outreach efforts. However, after learning about its existence, the community expressed the need for Posbakum as an alternative way to obtain legal assistance, especially in the context of legal problems. The conclusion highlights the importance of outreach efforts, providing information, and the role of Posbakum in providing access to justice. Therefore, this research contributes to the understanding of the effectiveness of Posbakum and its implications in the context of legal services at the local level.